Genome Sequence of Strain IMCC1989, a Novel Member of the Marine Gammaproteobacteria - Jang, Yoonra (American Society for Microbiology, 2011)
Strain IMCC1989 is a novel member of the oligotrophic marine Gammaproteobacteria (OMG) group and is closely related with a symbiont group of the genera Teredinibacter and “Candidatus Endobugula.” Here we present the genome sequence of strain IMCC1989, which was isolated from the Yellow Sea by using dilution-to-extinction culturing.